(untitled) (European Journal of Interdisciplinary Studies, 2021)
This paper is about the transformation in the patriarchal structure of Rashidpur village in Munshiganj district, Bangladesh following overseas migration of men leaving their women in the village. In doing so, the study explores the continuity and changes in the discourse and practices of traditional gender roles in a patriarchal Muslim society considering the perspective of both men and women. The study pays especial attention to transnational communication of the villagers, the changes in their gender based mobility and its contribution to the changes in patriarchal ideology. The study is based on ethnographic fieldwork, which examines whether the changes are sustainable or temporal for a period when the husbands are abroad and what happens to the practices when the husbands permanently return. Though the findings of the study indicate the diversity and complexity of practices, migration of men increases the mobility of the left behind women. Again, the entrance of cell phone, TV and satellite channels and transnational communication of women have significantly changed their agency as individuals. Consequently, many young wives like to come out of the domination of their in-laws and live in separate households instead of previous joint arrangement. The overall findings of the study show a remarkable change in the traditional pattern of village life. The study contextualizes structure and agency to understand how patriarchal structure influences individuals and how individuals play a role to transform the structure in exchange through their mobility, activities and resistance when the migrants are abroad.